Colonial Impotence : Virtue and Violence in a Congolese Concession (1911–1940) - Henriet, Benoît (2021)
In Colonial Impotence, Benoît Henriet studies the violent contradictions of colonial rule from the standpoint of the Leverville concession, Belgian Congo’s largest palm oil exploitation. Leverville was imagined as a benevolent tropical utopia, whose Congolese workers would be "civilized" through a paternalist machinery. However, the concession was marred by inefficiency, endemic corruption and intrinsic brutality. Colonial agents in the field could be seen as impotent, for they were both unable and unwilling to perform as expected. This book offers a new take on the joint experience of colonialism and capitalism in Southwest Congo, and sheds light on their impact on local environments, bodies, societies and cosmogonies.